Pemimpin Yang Melayani Menurut Markus 10:42-45 Dan Relevasinya Bagi Kepemimpinan Kristen Masa Kini - Anessa Mei Pasaribu; Asima Putri Handayani Nababan; Ibelala Gea (Jurnal Pendidikan Agama dan Teologi, 2023)
Leadership is the ability and readiness of a person to be able to influence, encourage, invite, demand, move and direct people or groups to receive this influence to achieve a goal. The purpose of this study is to describe servant leaders according to Mark 10:42-45 besides that, this research also provides good basic knowledge about leadership and the relevance of servant leaders for today's Christian leaders. The research method used by the author in writing this scientific work uses a qualitative research method, namely by means of literature study techniques, and case studies, namely digging up information from the Bible, books and journals regarding servant leaders according to Mark 10:42-45 and their relevance to today's Christian leadership , then confronted with the current form of application of Christian leadership as a leader who wants to serve. Namely a leader who serves, not a leader who rules with an iron fist or violence and rules with power, but a leader as a servant who has sincere feelings, is humble, has a heart as a servant, is willing to sacrifice both in time and energy. Servant leaders are leaders who give, affirm, strengthen, encourage, and sustain.